MIBG (metaiodobenzylguanidine) theranostics in pediatric and adult malignancies - Agrawal, Archi (Br J Radiol, 2018)
Metaiodobenzylguanidine, a guanithidine analog, labeled with (123)I and (131)I, is used for imaging and therapy of neuroblastomas and various neural crest tumors like paragangliomas, pheochromocytomas, medullary cancer of thyroid and carcinoids since the past three to four decades. In this review article, we shall revisit metaiodobenzylguanidine as a radiopharmaceutical and its various applications in neural crest tumors.